Origin and Evolution of Dendritic Epidermal T Cells - Sutoh, Yoichi; Mohamed, Rania Hassan; Kasahara, Masanori (Frontiers in Immunology, 2018)
Dendritic epidermal T cells (DETCs) expressing invariant Vγ5Vδ1 T-cell receptors play a crucial role in maintaining skin homeostasis in mice. When activated, they secrete cytokines, which recruit various immune cells to sites of infection and promote wound healing. Recently, a member of the butyrophilin family, Skint1, expressed specifically in the skin and thymus was identified as a gene required for DETC development in mice. Skint1 is a gene that arose by rodent-specific gene duplication. Consequently, a gene orthologous to mouse Skint1 exists only in rodents, indicating that Skint1-dependent DETCs are unique to rodents. However, dendritic-shaped epidermal γδ T cells with limited antigen receptor diversity appear to occur in other mammals. Even lampreys, a member of the most primitive class of vertebrates that even lacks T-cell receptors, have γδ T-like lymphocytes that resemble DETCs. This indicates that species as divergent as mice and lampreys share the needs to have innate-like T cells at their body surface, and that the origin of DETC-like cells is as ancient as that of lymphocytes.